Humic Substances Derived From Biomass Waste During Aerobic Composting and Hydrothermal Treatment: A Review - Hu, Zhong-Ting; Huo, Weizhong; Chen, Yue; Zhang, Qiang; Hu, Mian; Zheng, Weicheng; Shao, Yuchao; Pan, Zhiyan; Li, Xiaonian; Zhao, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Humic substances (HSs) occupy 80% of organic matter in soil and have been widely applied for soil remediation agents, potential battery materials and adsorbents. Since HSs extraction rate is very low by microbial degradation in nature, artificial humification processes such as aerobic composting (AC) and hydrothermal treatment (HT) have attracted a great deal of attention as the most important strategies in HSs production. This article aims to provide a state-of-the-art review on the development of conversion of biomass waste into HSs based on AC and HT for the first time in terms of mechanisms, characteristics of HSs' molecule structure and influence factors. Besides, some differences based on the above information between AC and HT are pioneering reviewed and discussed in the conversion of biomass waste into HSs. For biomass waste conversion, a feasible strategy on effective humification processes by combining AC with HT is proposed.